2008
DOI: 10.1111/j.1360-0443.2008.02210.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between cannabis abuse and dependence and childhood physical and sexual abuse: evidence from an offspring of twins design

Abstract: Aims-This study examines the association between childhood physical abuse (CPA) and sexual abuse (CSA) and the development of cannabis abuse and dependence among adolescents and young adults while controlling for genetic and environmental risk factors.Design-To control for familial risk differences related to paternal drug dependence that might confound the relationship between CSA and CPA and cannabis abuse/dependence, we created four groups based on father's and uncle's substance use dependence (SUD) status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 38 publications
9
62
1
10
Order By: Relevance
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 75%
“…Rates of MDD (Dinwiddie et al, 2000;Kendler et al, 2000;McCutcheon et al, 2009;Nelson et al, 2002), CD (Afi fi et al, 2009;Fergusson et al, 1996a;Molnar et al, 2001), cannabis and other illicit drug use disorders (Duncan et al, 2008;Kendler et al, 2000;Kilpatrick et al, 2000) and smoking (Al-Mamun et al, 2007;Anda et al, 1999;Nelson et al, 2006) are elevated in trauma-exposed populations. Thus, in examining the relationship between PTSD and alcohol-related outcomes, it is critical to adjust for the potential confounding effects of these commonly co-occurring conditions on the association of both PTSD and trauma exposure with AUDs.…”
mentioning
confidence: 99%
“…Of the 7 articles not included in Table 3, 5 of them (Scherrer et al, 2012a; Scherrer et al, 2012b;Sartor et al 2008;Sartor et al 2010;) are concerned with predictors of smoking behaviors and, while the primary research question of each is distinct, they all include the same CoT data/analyses -that was first included in Volk et al (2007). Similarly 2 articles concerned with drug dependence (Scherrer et al, 2008a; 2008b) repeat analyses included in Duncan et al (2008). Results are arranged in alphabetical order of first author.…”
Section: A Systematic Review Of Cot Studiesmentioning
confidence: 99%
“…They were interested in the association between the experience of abuse during childhood and later cannabis abuse/dependence in the offspring of the VETR sample. By using information on the drug dependence history of the (twin) parents Duncan et al (2008) were able to control for the genetic susceptibility towards drug dependence and the environmental risks associated with having a drug dependent father. Results showed that childhood sexual abuse predicted cannabis abuse/dependence above and beyond the genetic and familial risks associated with having a drug dependent father.…”
Section: Alternative Uses Of Cot Datamentioning
confidence: 99%
See 1 more Smart Citation